2011
DOI: 10.1021/ar200020s
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate Adsorbates for Self-Assembled Monolayer Films

Abstract: The spontaneous adsorption of organic molecules on a variety of planar and nonplanar substrates, that is, self assembly, can generate films just one molecule thick. These nanoscale, self-assembled monolayer (SAM) films have been extensively used to engineer surfaces with well-defined properties. Their utility has been demonstrated in a wide range of applications, including wetting, adhesion, lubrication, patterning, and molecular recognition. Many SAM systems have been investigated, but alkanethiols adsorbed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
172
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(175 citation statements)
references
References 84 publications
1
172
0
2
Order By: Relevance
“…By increasing the number of ligating groups per molecule, the equilibrium constant of ligand adsorption to the QD surface can theoretically increase exponentially [210, 211]. While quantitative studies are sparse, binding strengths have been observed to be slightly higher for ligands containing two thiols to gold surfaces [212] and to QDs [98]. However in molecular ligands, the flexibility needed to maximize binding affinity [210] may be difficult to achieve and the binding groups typically take up a larger footprint area on the QD surface which can reduce ligand packing density [213].…”
Section: Surface Engineering For Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By increasing the number of ligating groups per molecule, the equilibrium constant of ligand adsorption to the QD surface can theoretically increase exponentially [210, 211]. While quantitative studies are sparse, binding strengths have been observed to be slightly higher for ligands containing two thiols to gold surfaces [212] and to QDs [98]. However in molecular ligands, the flexibility needed to maximize binding affinity [210] may be difficult to achieve and the binding groups typically take up a larger footprint area on the QD surface which can reduce ligand packing density [213].…”
Section: Surface Engineering For Biomedical Applicationsmentioning
confidence: 99%
“…Compared with molecular multidentate ligands, the backbones can be more flexible and the number of binding domains can be much greater to allow improved attachment to the surface. Moreover, the density of hydrophilic domains and binding domains can be chosen independently to tune packing parameters and to append a variety of chemistries together on the same molecular backbone, as it is challenging to achieve a chemically mixed surface using molecular thiolates that may phase separate on surfaces [212, 216]. …”
Section: Surface Engineering For Biomedical Applicationsmentioning
confidence: 99%
“…There have been many investigations on the characterization and manipulation of alkylthiol SAMs on noble metals and the properties of the interface have been included in a variety of reviews [3][4][5][6][7][8]. Recently, the interest in Au-thiol chemistry has been renewed due its relation to nanotechnology as it was discovered that alkylthiols are efficient stabilizing ligands for gold nanoparticles (AuNPs) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, other types of adsorbates having multiple headgroup-metal interaction points have also been developed and studied [37][38][39]. Bidentate adsorbates have been introduced into surface chemistry due to their ability to enhance the stability of thin films formed on solid substrates [40].…”
Section: Introductionmentioning
confidence: 99%